Coupled disease-vaccination behavior dynamic analysis and its application in COVID-19 pandemic. (April 2023) - Meng, Xueyu; Lin, Jianhong; Fan, Yufei; Gao, Fujuan; Fenoaltea, Enrico Maria; Cai, Zhiqiang; Si, Shubin
Abstract: Predicting the evolutionary dynamics of the COVID-19 pandemic is a complex challenge. The complexity increases when the vaccination process dynamic is also considered. In addition, when applying a voluntary vaccination policy, the simultaneous behavioral evolution of individuals who decide whether and when to vaccinate must be included. In this paper, a coupled disease-vaccination behavior dynamic model is introduced to study the coevolution of individual vaccination strategies and infection spreading. We study disease transmission by a mean-field compartment model and introduce a non-linear infection rate that takes into account the simultaneity of interactions. Besides, the evolutionary game theory is used to investigate the contemporary evolution of vaccination strategies. Our findings suggest that sharing information with the entire population about the negative and positive consequences of infection and vaccination is beneficial as it boosts behaviors that can reduce the final epidemic size. Finally, we validate our transmission mechanism on real data from the COVID-19 pandemic in France. Highlights: A new couple disease-vaccination behavior model is introduced. A compartment model with a new nonlinear infection rate is proposed to study the disease transmission. An evolutionary game theory approach is implemented to study the simultaneous evolution of people vaccination strategies. Two rules for updating vaccination strategy are studied: one based on local imitation; the other based on global considerations. The infection transmission mechanism is validated with French COVID-19 data.